Correlation of autoantibodies with the Disease Activity Score 28 and radiographic hand joint damage in rheumatoid arthritis patients - Manuaba, Ida Ayu Ratih Wulansari; Sumariyono, Sumariyono; Isbagio, Harry (Indonesian Journal of Rheumatology, 2010)
Background: Rheumatoid arthritis (RA) is a systemic chronic infl ammatory disease of the joint that causes deformity or disability leading to a decreased function in RA patients. According to the 1987 American College of Rheumatology, rheumatoid factor (RF) is used as one of the diagnostic criteria because until today it is still considered as the primary autoantibody in RA although it has a lower specifi city than that of anticyclic citrullinated peptide (anti-CCP). Besides RF and anti-CCP, anti-RA33 is another autoantibody found. Thepresence of the three autoantibodies in RA patient serum is important because it is the starting point of the pathogenesis of the autoimmune process in RA.Methods: This is a cross-sectional study using consecutive sampling. Forty six subjects, all suffering from RA, were recruited for this study. All of them were tested for RF, anti-CCP, anti-RA33 titers using enzymelinked immunosorbent assay (ELISA) method and hadtheir hand radiograph taken to obtain the Sharp score to evaluate joint damage. During this study, 28-joint Disease Activity Score (DAS28) (4 parameters) was also evaluated using erythrocyte sedimentation rate as one of the parameters.Results: The study found that the correlation between the three antibodies and DAS28 was not statistically signifi cant: RF (r = 0.200, p = 0.091), anti-CCP (r =0.117, p = 0.220), and anti-RA33 (r = 0.126, p = 0.202). There was a signifi cant correlation between antiCCP and the Sharp score (r = 0.300, p = 0.021). The correlation between the other two autoantibodies and the Sharp score was not statistically significant:RF (r = 0.194, p = 0.098), anti-RA33 (r = 0.156, p = 0.150).Conclusion: There was a signifi cant correlation between anti-CCP autoantibody andÂ  radiographic hand joint damage in RA patients so that it could be used as an indicator for occurrence of an erosive or a more severe RA.